Neurodegenerative Diseases - Ciaccio, Marcello; Agnello, Luisa (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Neurodegenerative diseases (NDs) are a heterogeneous group of complex diseases characterized by neuronal loss and progressive degeneration of different areas of the nervous system. NDs represent a significant health problem worldwide, with an increasing incidence rate. Although the exact pathogenesis of NDs remains unclear, a complex interaction among genetic, epigenetic, and environmental factors has been proposed. To date, no effective therapeutics have been developed to slow, halt, or prevent any NDs. Thus, information on the molecular mechanisms underlying the pathogenesis of NDs is strongly sought after. This Special Issue collected papers discussing advances in the field of NDs.